The Bhabha Scattering in the Randall-sundrum Model - Thuc, Le Nhu (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4, 2018)
The change in other two fermion processes is called Bhabha process. In this paper, we discuss the Bhabha process  in the Randall –Sundrum (RS). We caculated the cross section for photon , boson Z, radion  and Higgs h exchange and evaluated exchange contributions of the Bhabha process in detail.  Keywords: DCS, cross-section, Bhabha, radion, Randall-Sundrum. References [1] L. Randall and R. Sundrum, Phys. Rev. Lett. 83, 3370, 1999. [2] H. Davoudiasl, T. McElmurry and A. Soni, Phys. Rev. D82, 115028, 2010. [3] V. P. Goncalves and W. K. Sauter, Phys. Rev. D82, 056009, 2010. [4] W. -J. Zhang, W. -G. Ma, R. -Y. Zhang, X. -Z. Li, L. Guo, and C. Chen, Phys. Rev. D92, 116005, 2015, [arXiv:1512.01766]. [5] C. Cai, Z.-H. Yu and H.-H. Zhang, Phys. Rev. D93. 075033, 2016. [6] F. Abu-Ajamieh, R. Houtz, and R. Zheng, [arXiv: 1607.01464v1 [hep-ph]], 2016. [7] The CMS Collaboration, CERN, August 2016. [8] The CMS Collaboration, CERN, September 2016. [9] F. Richard, [ arXiv:1804.02846 [hep-ex]], 2018.